JJCO Best Reviewer Award (Japanese Journal of Clinical Oncology, 2020)
OBJECTIVES: Spread through air spaces (STAS) is a poor prognostic pathological feature recently included as a histological factor in the ninth edition of the TNM (tumor, node, and metastasis) classification. However, its clinical significance in lung adenocarcinoma with epidermal growth factor receptor (EGFR) gene mutations remains unclear. Here, we aimed to evaluate the clinical significance of STAS according to EGFR mutation status. METHODS: We retrospectively reviewed 347 patients with completely resected pathological stage 0-IIIB lung adenocarcinoma who were evaluated for both STAS and EGFR mutations between 2015 and 2022. We investigated the association between clinicopathological features and STAS and analyzed its prognostic relevance based on EGFR mutation status. RESULTS: STAS and EGFR mutations were present in 85 (24.5%) and 178 (51.3%) patients, respectively. In patients with EGFR-mutated lung adenocarcinoma, STAS was significantly more prevalent in those with exon 19 deletions than those with the L858R mutation (P = .012). STAS was significantly markedly associated with poorer recurrence-free and overall survival in patients both with (P < .001 and P < .001, respectively) and without (P = .003 and P = .023, respectively) EGFR mutations. Multivariable analysis revealed that STAS was an independent prognostic factor for recurrence-free and overall survival in patients with EGFR mutations (P < .001 and P = .020, respectively). However, STAS was not an independent predictor in patients without EGFR mutations. CONCLUSIONS: STAS is a key pathological feature of lung adenocarcinoma and holds considerable clinical relevance, particularly in EGFR-mutated lung adenocarcinoma.